The Effects of Different Feeding Routines on Welfare in Laboratory Mice - Feige-Diller, Janina; Krakenberg, Viktoria; Bierbaum, Louisa; Seifert, Leonie; Palme, Rupert; Kaiser, Sylvia; Sachser, Norbert; Richter, S. Helene (Frontiers in Veterinary Science, 2020)
The accepted norm in most laboratories around the globe is feeding laboratory mice an ad libitum diet, although several health impairments are well-established. In contrast, reducing the animals’ body weight by feeding them less food once per day (referred to as 24 h schedule) has been shown to enhance life span and reduce disease susceptibility. Against this background, this study aimed at systematically investigating the effects of different feeding routines. Therefore, three feeding routines were compared to the standard ad libitum feeding and effects on body weight development and welfare were investigated in male C57BL/6J mice. In particular, a 24 h schedule group, an AUTO group, characterized by an automated supply of small pieces of food all over the day, and a 4 h removal group, characterized by daily removal of food for 4 hours, were studied. While the removal of food for 4 hours per day did not lead to a reduction of body weight, and hence is unlikely to prevent negative effects of overfeeding, both the 24 h schedule group and the AUTO group led to the aspired body weight reduction. In the AUTO group, however, higher levels of corticosterone metabolites and stereotypies were observed, implying a rather negative impact on welfare. By contrast, no distinct negative effects of a 24 h schedule were found. Studies like this underline the general need for evidence-based severity assessments of any procedure involving living animals.